USING THE CASE STUDY METHOD IN TEACHING COMPUTER SCIENCES AND INFORMATION TECHNOLOGIES AT SCHOOL - Karimov Kayum Mamashayevich (Bright Mind Publishing, 2025)
The article presents ideas for organizing the teaching of computer science and information technology to schoolchildren using the case method. The process of forming schoolchildren informational knowledge and skills was analyzed.
Keywords: Technology, interactive method, cases